A Case of Metastatic Pancreas Tumor from Papillary Carcinoma of Thyroid Treated by Hand-assisted Laparoscope Surgery (HALS) Distal Pancreatectomy with Splenectomy - Yamada, Takuya; Kato, Yoshihiko; Sakamoto, Kenichi; Kimura, Masaki; Takemura, Hirofumi; Sekino, Takafumi (The Japanese Journal of Gastroenterological Surgery, 2012)
We present a case of a 65-year-old woman with high standardized uptake value (SUV) in the tail of the pancreas on fluoro-deoxyglucose-positron-emission tomography (FDG-PET). She had undergone right lobectomy of the thyroid 2 years and a half previously due to papillary carcinoma of the thyroid. A year after that surgery, local papillary carcinoma of the thyroid recurred. She experienced difficulty in breathing and required emergency tracheotomy and repeated tumor resection. One year and a half after tracheotomy, the cancer recurred in mediastinal and neck lymph nodes, and lymph node dissection was performed. Three months after lymph node dissection, she underwent fine needle aspiration biopsy following identification of high SUV in the tail of the pancreas on FDG-PET. Metastasis from the papillary carcinoma of the thyroid was diagnosed in the tail of the pancreas. As no distant metastases were apparent, hand-assisted laparoscopic surgery (HALS) distal pancreatectomy with splenectomy was performed. Histopathological examination confirmed the diagnosis of metastatic tumor from the papillary carcinoma of the thyroid. Postoperative course was uneventful and the patient was discharged 10 days after surgery. Resectable metastatic pancreatic tumor from the thyroid is rare, and no reports have described metastatic pancreatic tumors from the thyroid treated using HALS. This patient has remained alive without relapse for 18 months after HALS.